Proteomic Analysis of Urine in Rats Chronically Exposed to Fluoride - Nakai Kobayashi, Claudia Ayumi; Leite, Aline de Lima; da Silva, Thelma Lopes; dos Santos, Lucilene Delazari [UNESP]; Sousa Nogueira, Fabio Cesar; Santos, Keity Souza; de Oliveira, Rodrigo Cardoso; Palma, Mario Sergio [UNESP]; Domont, Gilberto Barbosa; Rabelo Buzalaf, Marilia Afonso (Wiley-Blackwell, 2011)
Urine is an ideal source of materials to search for potential disease-related biomarkers as it is produced by the affected tissues and can be easily obtained by noninvasive methods. 2-DE-based proteomic approach was used to better understand the molecular mechanisms of injury induced by fluoride (F(-)) and define potential biomarkers of dental fluorosis. Three groups of weanling male Wistar rats were treated with drinking water containing 0 (control), 5, or 50 ppm F(-) for 60 days (n = 15/group). During the experimental period, the animals were kept individually in metabolic cages, to analyze the water and food consumption, as well as fecal and urinary F excretion. Urinary proteome profiles were examined using 2-DE and Colloidal Coomassie Brilliant Blue staining. A dose-response regarding F(-) intake and excretion was detected. Quantitative intensity analysis revealed 8, 11, and 8 significantly altered proteins between control vs. 5 ppm F(-), control vs. 50 ppm F(-) and 5 ppm F(-) vs. 50 ppm F(-) groups, respectively. Two proteins regulated by androgens (androgen-regulated 20-KDa protein and 0c-2,1-globulin) and one related to detoxification (aflatoxin-Bl-aldehyde-reductase) were identified by MALDI-TOF-TOF MS/MS. Thus, proteomic analysis can help to better understand the mechanisms underlying F(-) toxicity, even in low doses. 2010 Wiley Periodicals, Inc. J Biochem Mol Toxicol 25:8-14, 2011; View this article online at wileyonlinelibrary.com. DOI 10:1002/jbt.20353
Keywords: Proteomics; Mass Spectrometry; Two-Dimensional Electrophoresis; fluoride; Urine; Biomarker